(4x + 2y) - [3x - 5(x - 3y)]
(4x + 2y) - [3x - 5x + 15y]
4x + 2y - 3x + 5x - 15y
6x - 13y
2007-03-21 03:37:43
·
answer #1
·
answered by Bhajun Singh 4
·
0⤊
0⤋
Let us proceed
(4x+2y) - {3x-5(x-3y)} needs to be properly spaced, like this:
( 4x + 2y ) - { 3x - 5 ( x - 3y ) }
= + 4x + 2y - { 3x - 5x + 15y }
= + 4x + 2y - 3x + 5x - 15y
= + 4x - 3x + 5x + 2y - 15 y
= + (9 - 3)x + (2 - 15) y
= 6x - 13y
done
2007-03-21 10:43:05
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
(4x + 2y) - (3x - 5(x-3y) =
(4x + 2y ) - (3x -5x + 15y) =
(4x + 2y) - 3x + 5x - 15y =
4x + 2 y + 2x - 15y =
6x - 13y
2007-03-21 10:47:11
·
answer #3
·
answered by detektibgapo 5
·
0⤊
0⤋
(4x + 2y) - {3x - 5(x - 3y)
4x + 2y - {3x -(5x - 15y)
4x + 2y - {3x - 5x + 15y}
4x + 2y - 3x + 5x - 15y
4x - 3x + 5x + 2y - 15y
x + 5x - 13y
6x - 13y
- - - - - - - - s-
2007-03-21 11:47:52
·
answer #4
·
answered by SAMUEL D 7
·
0⤊
0⤋
(4x+2y) - [3x-5x+15y]
(4x+2y) - (-2x) +15y
4x + 2y + 2x + 15y
answer: 6x + 17y
2007-03-21 10:43:11
·
answer #5
·
answered by b_mayoh 1
·
0⤊
0⤋
(4x+2y) - {3x-5(x-3y)} =
(4x + 2y) - {3x - 5x + 15y} =
4x + 2y - 3x + 5x - 15y =
6x -13y
..::..
2007-03-21 11:02:59
·
answer #6
·
answered by aeiou 7
·
0⤊
0⤋
= (4x + 2y) - (3x -5x + 15y)
= (4x + 2y) - (-2x + 15y)
= 4x + 2y + 2x + 15y
= 6x + 17y
=:)
2007-03-21 10:44:23
·
answer #7
·
answered by morgan 2
·
0⤊
0⤋
I get 6x-13y
but it has been quite a few years since I've been in Algebra.
2007-03-21 10:39:37
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
(4x+2y)-{3x-5(x-3y)}
=(4x+2y)-(3x-5x+15y)
=4x+2y-3x+5x-15y
=4x-3x+5x+2y-15y
=6x-13y
2007-03-21 10:42:38
·
answer #9
·
answered by Bubblez 3
·
0⤊
0⤋
look in the back its what i did in college
2007-03-21 10:40:55
·
answer #10
·
answered by Juleette 6
·
0⤊
0⤋